New Insights on Streptococcus dysgalactiae subsp. dysgalactiae Isolates - Alves-Barroco, Cinthia; Caço, João; Roma-Rodrigues, Catarina; Fernandes, Alexandra R.; Bexiga, Ricardo; Oliveira, Manuela; Chambel, Lélia; Tenreiro, Rogério; Mato, Rosario; Santos-Sanches, Ilda (Frontiers in Microbiology, 2021)
Streptococcus dysgalactiae subsp. dysgalactiae (SDSD) has been considered a strict animal pathogen. Nevertheless, the recent reports of human infections suggest a niche expansion for this subspecies, which may be a consequence of the virulence genes acquisition that increase its pathogenicity. Previous studies reported the presence of virulence genes of Streptococcus pyogenes phages among bovine SDSD (collected in 2002-03); however, the identity of these mobile genetic elements remains to be clarified. Thus, this study aimed to characterize the SDSD isolates collected in 2011-2013 and compare them with SDSD isolates collected in 2002-2003 and pyogenic streptococci genomes available at NCBI database, including human SDSD and S. dysgalactiae subsp. equisimilis (SDSE) strains to track temporal shifts on bovine SDSD genotypes. The very close genetic relationships between humans SDSD and SDSE were evident from the analysis of housekeeping genes, while bovine SDSD isolates seem more divergent. The results showed all bovine SDSD harbour CRISPR-Cas IIA system. The widespread presence of this system among bovine SDSD isolates, high conservation of repeat sequences, and the polymorphism observed in spacer can be considered indicators of the system activity. Overall, comparative analysis showns that bovine SDSD isolates carriage speK, speC, speL, speM, spd1, and sdn virulence genes of S. pyogenes prophages. Our data suggest that these genes are maintained over time and seem to be exclusively a property of bovine SDSD strains. Although the bovine SDSD genomes characterized in the present study were not sequenced, the data set, including the high homology of SAgs genes between bovine SDSD and S. pyogenes strains, may indicate that events of horizontal genetic transfer occurred before habitat separation. All bovine SDSD isolates were negative for genes of operon encoding streptolysin S, except for the sagA gene, while the presence of this operon was detected in all SDSE and human SDSD strains. The data set of this study suggest that the separation between the subspecies "dysgalactiae" and "equisimilis" should be reconsidered. However, a study including the most comprehensive collection of strains from different environments would be required for definitive conclusions regarding the two taxa.